An Analysis of Register Elements and Language Functions in an English Educational YouTube Video: Analisis Unsur Register dan Fungsi Bahasa dalam Video Edukasi Bahasa Inggris di YouTube - Amaryllis Dwi Kurnia; Zulfa Nabila (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2026)
The growth of English educational YouTube videos has made language learning more flexible, multimodal, and accessible. This study examines how register elements and Halliday’s language functions are realized in an English educational YouTube video. The data consisted of the instructor’s utterances in an mmmEnglish lesson about making and rescheduling appointments by phone. This research used a descriptive qualitative case study design grounded in Systemic Functional Linguistics. Data were collected through documentation of a verified transcript and analyzed using Miles, Huberman, and Saldaña’s interactive model. The analysis focused on field, tenor, and mode, as well as instrumental, regulatory, representational, interactional, personal, heuristic, and imaginative functions. The findings show that the video constructs instructional meaning through clear lesson content, supportive instructor–learner relations, and spoken digital delivery. Instrumental and representational functions appear prominently because the lesson combines practical speaking practice with explicit explanation. This study implies that effective digital English instruction depends on the integration of context, communicative purpose, and pedagogical design.